2010
DOI: 10.1002/wrna.13
|View full text |Cite
|
Sign up to set email alerts
|

Networks controlling mRNA decay in the immune system

Abstract: The active control of mRNA degradation has emerged as a key regulatory mechanism required for proper gene expression in the immune system. An adenosine/uridine (AU)-rich element (ARE) is at the heart of a first regulatory system that promotes the rapid degradation of a multitude of cytokine and chemokine mRNAs. AREs serve as binding sites for a number of regulatory proteins that either destabilize or stabilize the mRNA. Several kinase pathways regulate the activity of ARE-binding proteins and thereby coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 249 publications
(277 reference statements)
1
56
1
Order By: Relevance
“…Such a process of regulation, already described for different miRNAs, 40 suggests that miRNAs act as key gene switches and as fine-tuning molecules, depending on the compartment and the specific biologic context. 20 Therefore, our data suggest that mir-142-3p is also implicated in the TGF-b pathway. However, because the modulation of one miRNA may affect multiple mRNAs that are also regulated by several other miRNAs, a direct link between these two molecules cannot be predicted at this stage.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Such a process of regulation, already described for different miRNAs, 40 suggests that miRNAs act as key gene switches and as fine-tuning molecules, depending on the compartment and the specific biologic context. 20 Therefore, our data suggest that mir-142-3p is also implicated in the TGF-b pathway. However, because the modulation of one miRNA may affect multiple mRNAs that are also regulated by several other miRNAs, a direct link between these two molecules cannot be predicted at this stage.…”
Section: Discussionmentioning
confidence: 62%
“…16,17 Furthermore, the incomplete pattern of target recognition allows a single miRNA to target hundreds of mRNAs, and conversely, a single mRNA to be targeted by multiple miRNAs, thus affecting a broad range of gene networks. 18 Numerous studies have reported on the differential expression of miRNA in physiologic disorders or diseases, 19,20 and miRNA has been found to be modulated in biopsy specimens from kidney transplant recipients. [21][22][23] In this study, we investigated whether miRNA is modulated in the blood of patients with operational tolerance compared with a cohort of patients with stable graft function under classic immunosuppression.…”
mentioning
confidence: 99%
“…Despite this regulatory potential, we initially remarked no difference in the lengths of 3′ UTRs (Figure 3). The density of AU-rich elements was similar; however, our analyses could not take into account the distinction between AU elements involved in rapid decay and finer stability regulation (46). Greater GC content was found in nonsource 3′ UTRs and along the entire mRNA transcript in general; this may reflect a positive association with mRNA levels in a degradation-independent manner (47).…”
Section: Resultsmentioning
confidence: 99%
“…Based on models of the kinetics of mRNA accumulation (Elkon et al 2010), the alterations in mRNA half-lives that we observe during flavivirus infections are likely to have a much greater influence on the expression of naturally short-lived mRNAs as compared with longer-lived transcripts. Interestingly, many cytokines and factors involved in aspects of innate immunity are often encoded by short-lived transcripts (Schott and Stoecklin 2010). Thus flaviviruses may use this strategy to disturb the normal regulation of these factors and escape cellular surveillance mechanisms that would normally limit their replication and perhaps induce immunopathogenesis.…”
Section: Discussionmentioning
confidence: 99%